Biochemical correlate of dimorphism in a zygomycete benjaminiella poitrasii: characterization of purified NAD-dependent glutamate dehydrogenase, a target for antifungal agents - Joshi, C. V.; Pathan, E. K.; Punekar, N. S.; Tupe, S. G.; Kapadnis, B. P.; Deshpande, Mukund V. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2013)
The fungal organisms, especially pathogens, change their vegetative (Y, unicellular yeast and H, hypha) morphology reversibly for survival and proliferation in the host environment. NAD-dependent glutamate dehydrogenase (NAD-GDH, EC 1.4.1.2) from a non-pathogenic dimorphic zygomycete Benjaminiella poitrasii was previously reported to be an important biochemical correlate of the transition process. The enzyme was purified to homogeneity and characterized. It is a 371 kDa native molecular weight protein made up of four identical subunits. Kinetic studies showed that unlike other NAD-GDHs, it may act as an anabolic enzyme and has more affinity towards 2-oxoglutarate than l-glutamate. Chemical modifications revealed the involvement of single histidine and lysine residues in the catalytic activity of the enzyme. The phosphorylation and dephosphorylation study showed that the NAD-GDH is present in active phosphorylated form in hyphal cells of B. poitrasii. Two of the 1,2,3 triazole linked beta-lactam-bile acid conjugates synthesized in the laboratory (B18, B20) were found to be potent inhibitors of purified NAD-GDH which also significantly affected Y-H transition in B. poitrasii. Furthermore, the compound B20 inhibited germ tube formation during Y-H transition in Candida albicans strains and Yarrowia lipolytica. The possible use of NAD-GDH as a target for antifungal agents is discussed.
Keywords: Antifungal agent; Benjaminiella poitrasii; Biochemical correlate of dimorphism; Candida albicans; NAD-GDH activity regulation; Yarrowia lipolytica; Yeast-hypha reversible transition

Determination of the effect of polyamines on an oil-degrading strain of Yarrowia lipolytica using an odc minus mutant - Campos-Gongora, E.; Palande, A. S.; Leon-Ramirez, C.; Pathan, E. K.; Ruiz-Herrera, J.; Deshpande, M. V. (Fems Yeast Research, 2018)
Yarrowia lipolytica is an ascomycetous dimorphic yeast with immense potential for industrial applications, including bioremediation of crude oil-contaminated environments. It has been shown that a dimorphic marine isolate of Y. lipolytica (var. indica) has significant capacity to degrade fatty acids and alkanes, when in its yeast morphology. It has also been demonstrated that polyamines play an important role in the yeast-to-mycelium transition of different strains of Y. lipolytica that are unable to utilize those carbon sources. To determine the role of polyamines on their capacity to utilize oils and hydrocarbons, on the dimorphic transition, and also on other characteristics of the var. indica strain of Y. lipolytica, we proceeded to obtain ornithine decarboxylase minus (odc(-)) mutants. These mutants behaved as yeasts independently of the concentrations of putrescine added. Further, they conserved the oil-degrading capacity of the parent strain. The odc(-) mutant can thus be used in fatty acid degradation, and oil spill remediation with distinct advantages.

Bioprospecting of fungal entomo- and myco-pathogens - Pathan, E. K.; Patil, A. V.; Deshpande, M. V. (Advancing Frontiers in Mycology & Mycotechnology, 2019)
The pest and pathogen control in the field using fungi and their metabolites has indeed gone beyond ‘proof of concept’. However, in view of the performances of these biocontrol fungi in the fields, moreover, acceptability by the end users regarding cost-effectiveness, shelf life, intellectual property rights (IPR), the additional roles, and possible applications are being explored. Dual pathogenicity, viz. entomopathogenesis and mycoparasitism, has added the advantage of wide-spectrum biocontrol in single-crop system. In addition to plant protection, these fungi can promote plant growth. Further, in integrated pest management, the bioremediation of pesticide residues, if any, can also be achieved by these organisms. For value addition, use of cuticle-degrading and mycolytic enzymes produced as killing components can be explored in food, detergent, organic synthesis, and pharmaceutical industries. While exploring the additional applications, the safety to beneficial insects and fungi, biodiversity, and humans, in general, is also addressed.